Comprehensive model of linear PMSM-based ropeless lift for comparing control algorithms – Field-oriented control versus direct torque control. (November 2020) - So, Albert; Chan, Wai L
This is a further study of two previous articles of the authors. The simulation model includes saliency and almost all common imperfections of linear permanent magnet synchronous machine. Based on the same model, three types of control have been applied to drive the lift car for a typical fully loaded upward journey, namely field-oriented control, which was used in two previous articles, direct force control (conventional direct torque control on a linear machine) and a newly proposed direct speed control (a new direct torque control method that could be used in the lift industry). The performances in terms of speed accuracy during start-up and rated speed operation, power and energy consumption have been studied. The conclusion is that for such a new application in the lift industry, at this moment in time, the more conventional field-oriented control is highly recommended. Two new findings are reported. Direct speed control that involves a simpler circuitry and reasonable speed control is proposed, although there is always a small steady-state error due to the absence of a proportional–integral controller. Conventional direct torque (force) control involves continuous integration to estimate the magnetic fluxes, which is not applicable to a permanent magnet synchronous machine with saliency. A new definition to analytically estimate the magnetic flux linkages in real time is also proposed. It should be noted that field-oriented control is superior at this time. When technology continues to get advanced, direct force control and direct speed control may one day be more appropriate for linear permanent magnet synchronous machine application. The software to perform the simulation has been uploaded to the BSER&T/SAGE website. Practical application: It is generally agreed by the lift industry that the installation of multi-dimensional lifts employing linear permanent magnet synchronous machines is a clear trend in the future. This article is a follow up of two previous ones, studying the performance of three types of control for linear permanent magnet synchronous machine. Necessary equations of the machine model, imperfections, digital control loops are included. Some findings regarding the differences in performance are reported. It is hoped that this article is useful for lift manufacturers to enter this new market of vertical transportation.